Kajian Stilistika Uslūb Tafḍīl dalam Khutbah Imam Ali: Studi pada Nahjul Balaghah Jilid 1 - Aziza, Siti Nur; Edidarmo, Toto (STIQ Amuntai, 2025)
This study investigates the stylistic deployment of uslūb at-tafḍīl (comparative-superlative constructions) in selected sermons of Imam ʿAlī contained in Nahjul Balaghah, Volume I, as rendered into Indonesian by Muhammad Halabi. Employing a qualitative, stylistic-textual method, it maps how Arabic linguistic devices—especially ism tafḍīl—convey rhetorical force, ethical exhortation, and spiritual resonance, and examines the extent to which these effects survive translation. The data set comprises sermons that employ uslūb at-tafḍīl explicitly or implicitly; each is analysed for its grammatical form, rhetorical function (moral persuasion, social criticism, performative oath), and the shifts that occur in the target text. The findings reveal that tafḍīl transcends mere grammatical comparison, functioning as an evaluative, ideological, and pragmatic resource. The lexical and syntactic constraints of Indonesian attenuate certain nuances, especially moral intensity and emotive colouring, while Halabi's translation captures most of the expressive load. The article contributes to Arabic stylistics, Islamic rhetoric, and translation studies by underscoring the need to preserve stylistic integrity when mediating sacred discourse.